Electroporation of Alcaligenes eutrophus with (mega) plasmids and genomic DNA fragments. - Taghavi, S (1994)
Electroporation was used as a tool to explore the genetics of the heavy-metal-resistant strain Alcaligenes eutrophus CH34. A 12.9-kb A. eutrophus-Escherichia coli shuttle vector, pMOL850, was constructed to optimize electroporation conditions. This vector is derived from the E. coli plasmid pSUP202 and contains the replication region of the A. eutrophus megaplasmid pMOL28. Electroporation was used to transform A. eutrophus CH34 derivatives with megaplasmids (sizes up to 240 kb), and transformants were selected for resistance to heavy metals. Electroporation was also performed with endonuclease-digested genomic DNA. Transformation of markers affecting lysine biosynthesis (lysA194) and biosynthesis of the siderophore alcaligin E were observed. Transfer of the nonselected markers pheB332 and aro-333, linked to lysA194, confirmed the intervention of homologous recombination. However, during transformation of ale::Tn5-Tc, illegitimate recombination and transposition were also observed as an alternative for the inheritance of the Tn5-Tc markers.